2014
DOI: 10.5056/jnm14060
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Interstitial Cells in Neurogastroenterology

Abstract: Smooth muscle layers of the gastrointestinal tract consist of a heterogeneous population of cells that include enteric neurons, several classes of interstitial cells of mesenchymal origin, a variety of immune cells and smooth muscle cells (SMCs). Over the last number of years the complexity of the interactions between these cell types has begun to emerge. For example, interstitial cells, consisting of both interstitial cells of Cajal (ICC) and platelet-derived growth factor receptor alpha-positive (PDGFRα + ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
111
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 244 publications
(233 reference statements)
1
111
0
1
Order By: Relevance
“…Our Western blot data indicated that SRF levels increased after 2 weeks of partial obstruction but that MYH11 levels remained unchanged. 31,37 We found that each subtype was differentially remodeled during partial intestinal obstruction. However, further studies are needed to determine whether any of these subtypes can display plasticity in the remodeling response.…”
Section: Discussionmentioning
confidence: 88%
“…Our Western blot data indicated that SRF levels increased after 2 weeks of partial obstruction but that MYH11 levels remained unchanged. 31,37 We found that each subtype was differentially remodeled during partial intestinal obstruction. However, further studies are needed to determine whether any of these subtypes can display plasticity in the remodeling response.…”
Section: Discussionmentioning
confidence: 88%
“…Although located very close to ICC, ultrastructural and functional aspects of FLCs are distinct from those of ICC[21]. Located very close to nerve endings, FLCs are considered to have a role in neurotransmission, especially within purinergic neurotransmission[37,38]. In this study, whereas a decrease in FLCs was observed in the gastric body and fundus of the DM group, no difference in the numbers of FLCs was observed in the antrum of the DM group compared to that of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…19 The ECA of the small intestine is primarily generated by interstitial cells of Cajal (ICC) located in the muscularis. 26 The ECA governs when a muscle contraction can occur. Contractions are possible when the membrane potential is in a depolarized state and is prevented when in a hyperpolarized state.…”
Section: Discussionmentioning
confidence: 99%